Calcium Fertilization in Peanuts: Importance, Sources, and Considerations - Satinderpal Singh; Melinda Thoms; Hardeep Singh; Barry Tillman; Emma Matcham; Ethan Carter (EDIS)
This article examines the sources of calcium, application rate and timings of these sources, and their effect on peanut growth. The purpose of this article is to share knowledge about calcium fertilization in peanuts among crop advisors, Extension agents, and farmers. Written by Satinderpal Singh, Melinda Thoms, Hardeep Singh, Barry Tillman, Emma Matcham, and Ethan Carter, and published by the UF/IFAS Department of Agronomy, February 2025.